Export processing in Saint Lucia : owenership, linkages and transfer of technology. - WILLMORE, Larry (1995)
Presents an overview of the 18 export processing firms in Saint Lucia at the end of the first quarter of 1993. Notes that the US is the major market for all but two of the firms, and is also the predominant investor in export processing in Saint Lucia. Transfer of technology is done through training of the labour force, as well as through skills that are valuable for the development of the country to Saint Lucians occupying managerial and supervisory positions. Local ownership and forward linkages are absent, but many of the plant managers are nationals of Saint Lucia, and backward linkages are strong.